A review of genera Cryphia Hübner, 1818 and Bryophila Treitschke, 1825 within the mountainous Central Asia: a case of too many poorly described species (Lepidoptera: Noctuidae) - Korb, Stanislav K. (Zootaxa, 2020)
The genera Cryphia Hübner, 1818 and Bryophila Treitschke, 1825 in mountainous Central Asia (in the range of Kazakhstan, Kyrgyzstan and Tajikistan) are reviewed. Both molecular and morphological data are used. A short morphometric test of male genitalia within 3 widely distributed and common species processed (Bryophila sordida Staudinger, 1900, B. rueckbeili Boursin, 1953, B. plumbeola (Staudinger, 1881)); the vesica is quite variable, spike is less variable, valva is highly variable. The CO1 differences between studied species in Central Asia are over at least 0,02; the p-distances inside of B. plumbeola clade are no more than 0,003 and this is clear evidence of their conspecificity. The lectotypes of Bryophila miltophaea Hampson, 1908 and Bryophila subliterata Filipjev, 1931 are designated. The following new statuses are applied: Bryophila eucta hannemanni Boursin, 1961, stat. n., B. plumbeola hampsoni (Draudt, 1931), stat. n., B. plumbeola miltophaea (Hampson, 1908), stat. n., B. plumbeola puengeleri (Draudt, 1931), stat. n., B. plumbeola vilis (Hampson, 1908), stat. n. A new subspecies, B. raptricula montanotricula Korb, ssp. n., is described from Katta-Kaindy Mts., 8.5 km S of Englchek, 2509 m, N 41°57’518 E 79° 7’782. It differs from the subspecies B. raptricula aksuensis by its wing pattern (structure of the middle band and of the white strokes) and by DNA (CO1sequence). A list of Cryphia and Bryophila species erroneously placed into the mountainous Central Asiatic fauna is compiled.